The first genomic characterization of a stable, hemin-dependent small colony variant strain of Staphylococcus epidermidis isolated from a prosthetic-joint infection - Bogut, Agnieszka; Koper, Piotr; Marczak, Małgorzata; Całka, Paulina (Frontiers in Microbiology, 2023)
Phenotype switching from a wild type (WT) to a slow-growing subpopulation, referred to as small colony variants (SCVs), supports an infectious lifestyle of Staphylococcus epidermidis, the leading cause of medical device-related infections. Specific mechanisms underlying formation of SCVs and involved in the shaping of their pathogenic potential are of particular interest for stable strains as they have been only rarely cultured from clinical specimens. As the SCV phenotype stability implies the existence of genetic changes, the whole genome sequence of a stable, hemin-dependent S. epidermidis SCV strain (named 49SCV) involved in a late prosthetic joint infection was analysed. The strain was isolated in a monoculture without a corresponding WT clone, therefore, its genome was compared against five reference S. epidermidis strains (ATCC12228, ATCC14990, NBRC113846, O47, and RP62A), both at the level of the genome structure and coding sequences. According to the Multilocus Sequence Typing analysis, the 49SCV strain represented the sequence type 2 (ST2) regarded as the most prominent infection-causing lineage with a worldwide dissemination. Genomic features unique to 49SCV included the absence of the Staphylococcal Cassette Chromosome (SCC), ~12kb deletion with the loss of genes involved in the arginine deiminase pathway, and frameshift-generating mutations within the poly(A) and poly(T) homopolymeric tracts. Indels were identified in loci associated with adherence, metabolism, stress response, virulence, and cell wall synthesis. Of note, deletion in the poly(A) of the hemA gene has been considered a possible trigger factor for the phenotype transition and hemin auxotrophy in the strain. To our knowledge, the study represents the first genomic characterization of a clinical, stable and hemin-dependent S. epidermidis SCV strain. We propose that previously unreported indels in the homopolymeric tracts can constitute a background of the SCV phenotype due to a resulting truncation of the corresponding proteins and their possible biological dysfunction. Streamline of genetic content evidenced by the loss of the SCC and a large genomic deletion can represent a possible strategy associated both with the SCV phenotype and its adaptation to chronicity.